(Re)Searching for the development of a conceptual model of education for citizenship in the context of young people's globalised mobility in higher education. (15th March 2019) - Islam, Md Tariqul
ABSTRACT: This paper proposes a conceptual model of education for global citizenship by drawing on the literature on international student mobility for higher education. This model outlines the kinds of competencies and forms of consciousness that education for citizenship should focus upon so as to address the economic and moral dilemmas of living in a globalising world. In an integrative review process, this paper identifies the challenges and opportunities that globalised mobility brings to the lives of young people, the mobilities that higher educational institutions are embracing, the mobility motivations of young students in higher education, and the consequences of this globalised mobility for their present and future life.